2016
DOI: 10.1016/j.biomaterials.2015.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of in vivo tissue engineered blood vessels in a porcine model

Abstract: Autologous TEBVs were created in vivo with sufficient mechanical strength enabling vascular grafting. Grafts differentiated towards a vascular phenotype upon grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 48 publications
(64 reference statements)
2
61
0
Order By: Relevance
“…SMC’s are important in maintaining vascular homeostasis notably with regard to the vasoreactivity of vessels. Various studies have shown that after grafting, populations of (myo-)fibroblasts have either transdifferentiated to, of been replaced by SMC like cells [14, 58, 59, 66]. A histological overview of the differentiation of the tissue capsules towards blood vessel-like structures that we observed in our pig studies is provided in Figure 3.…”
Section: Remodeling Of Tebv After Implantation In the Circulationmentioning
confidence: 72%
See 4 more Smart Citations
“…SMC’s are important in maintaining vascular homeostasis notably with regard to the vasoreactivity of vessels. Various studies have shown that after grafting, populations of (myo-)fibroblasts have either transdifferentiated to, of been replaced by SMC like cells [14, 58, 59, 66]. A histological overview of the differentiation of the tissue capsules towards blood vessel-like structures that we observed in our pig studies is provided in Figure 3.…”
Section: Remodeling Of Tebv After Implantation In the Circulationmentioning
confidence: 72%
“…Monolayer of endothelium. Elastin like mesh seen.1085 mmHgIntroduction sheeth usedInteresting presence of elastinYamanami et al [71]Type C – mold systemDorsum - subcutaneousArgatroban610 mmFemale BeaglesFemoral artery end-to-endultrasonographyOriginal: biotube 33%Type C: 100%7 daysFibroblasts and collagen.Elastin present.Thick, collagen rich, elastin present.Original: biotube 944 mmHgType C: 1825 mmHgImprovement over original designFurukoshi et al [15]Silicone, fasciaMedial thigh - subcutaneousFascia covered1510 mmFemale Japanese white rabbitsFemoral artery end-to-endMilking test60%80%80%2 weeks5 weeks8 weeks-Fibroblast, endothelium ingrowth.-Interesting concept to incorporate dorsal fasciaTsukagoshi et al [16]PEOT/PBT 55/45Abdomen - subcutaneousChloroform etching880 mmFemale landrace pigsCarotid artery bilateral, end-to-endAngiography88%4 weeks(myo-)fibroblasts, ECM, some luminal macrophages.Predominantly desmin (+) SMC like cells, no leukocytes, Monolayer of endothelium, some elastin positivity.5211,04 mmHg (derived burst pressure)Biomaterial surface modification to tailor FBRRothuizen et al [14]α- SMA, alpha-smooth muscle actin; SMC, smooth muscle cell; vim, vimentin; des, desmin; FBR, foreign body response …”
Section: Overview Of Approaches For In Situ Vascular Tissue Engineeringmentioning
confidence: 99%
See 3 more Smart Citations